1989
DOI: 10.3109/17453678909149249
|View full text |Cite
|
Sign up to set email alerts
|

Knee laxity in cruciate ligament injury: Value of examination under anesthesia

Abstract: Arthrometry was performed before and during anesthesia in 41 patients with acute or old anterior cruciate ligament injuries and only minor signs of valgus or varus instability. The uninjured contralateral knee served as a control. The influence of anesthesia on the anterior stability was distinct in acute knee injuries. There was also a small, but definite, increase in anterior laxity in uninjured knees. Knees with old injuries were more lax, and the injured-uninjured difference in anterior laxity was more pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 8 publications
0
25
0
1
Order By: Relevance
“…Further, while patients were generally not reconstructed until the knee was calm, post-injury stiffness could potentially influence laxity assessments in patients reconstructed acutely; however, findings that laxity is increased in more chronic cases case been confirmed by prior work. (610) A more detailed assessment of the degree of generalized ligamentous laxity demonstrated by each patients (such as a Beighton score)(26) would also have been interesting to assess,; the collected data included on ly the IKDC classification of “tight”, “normal”, or “lax.”A final limitation of this study is the lack of specific details regarding the type of meniscus tears that were noted in each patient. Larger or more peripheral tears, as well as those located in the posterior horn of the menisci (particularly medially) may have a larger influence on the presence of high-grade knee laxity.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, while patients were generally not reconstructed until the knee was calm, post-injury stiffness could potentially influence laxity assessments in patients reconstructed acutely; however, findings that laxity is increased in more chronic cases case been confirmed by prior work. (610) A more detailed assessment of the degree of generalized ligamentous laxity demonstrated by each patients (such as a Beighton score)(26) would also have been interesting to assess,; the collected data included on ly the IKDC classification of “tight”, “normal”, or “lax.”A final limitation of this study is the lack of specific details regarding the type of meniscus tears that were noted in each patient. Larger or more peripheral tears, as well as those located in the posterior horn of the menisci (particularly medially) may have a larger influence on the presence of high-grade knee laxity.…”
Section: Limitationsmentioning
confidence: 99%
“…Previous work has demonstrated an increased incidence of a positive Lachman, anterior drawer, and pivot-shift in the setting of more chronic ACL injuries. (610) Previous studies have demonstrated a higher prevalence of lateral meniscus tears in patients with a high49 grade pivot-shift (11, 12) and in those with a positive anterior drawer test. (13) The influence of patient demographic factors on the findings of these pre-operative physical examination tests has not been explored in detail, although females have been noted to have increased anterior laxity in some series following ACL reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“…50,52 Overall, we analyzed 28 studies that met our inclusion criteria. 5,[8][9][10]12,13,18,20,26,27,30,32,34,35,38,39,42,44,48,50,52,55,60,61,63,69,71,72,74 Twenty-seven of these studies were identified in MEDLINE, 10 in EMBASE, and 1 in CINAHL.…”
Section: Methodological Quality and Study Characteristicsmentioning
confidence: 99%
“…MRI was used in 2 studies. 8,39 Furthermore, 14 studies applied arthroscopy 9,13,18,26,34,35,38,42,50,51,55,60,63,69,71 and 5 studies arthrotomy. 10,20,30,72,74 In just 3 studies there was independent, blind comparison of the index test with a reference standard of diagnosis and vice versa.…”
Section: Methodological Quality and Study Characteristicsmentioning
confidence: 99%
“…Using this difference as a tool to evaluate the surgical outcome, fewer patients returned to normal stability with RSA than with KT-1000. 133 N force or the maximum manual test with the KT-1000 (134-178 N, Daniel et al 1985b) result in greater side-to-side difference (Dahlstedt andDalkn 1989, Steiner et al 1990, Anderson et al 1992). However, Steiner et al (1990) reported unchanged diagnostic accuracy of chronic tears of the anterior cruciate ligament with 133 N. Thus, the use of different loads is probably not sufficient to explain the differences between the KT 1000 and RSA in this study.…”
mentioning
confidence: 99%